2015
DOI: 10.1007/s11325-015-1193-z
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality associated with obesity in men

Abstract: Sleep quality was negatively associated with overweight/obesity in Chinese men but not in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
4
12
1
Order By: Relevance
“…Contrary to a previous study on self-rated health status [28] , and in agreement with a previous study on happiness [34] , this study found an association between very healthy self-rated health status, very happy happiness status and having overweight or obesity. Moreover, unlike previous studies on depression [30] , [31] , this study found a negative association between depression and having overweight or obesity. Some previous study [33] found an association between poor sleep quality and having obesity, while this study did not find such an association.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to a previous study on self-rated health status [28] , and in agreement with a previous study on happiness [34] , this study found an association between very healthy self-rated health status, very happy happiness status and having overweight or obesity. Moreover, unlike previous studies on depression [30] , [31] , this study found a negative association between depression and having overweight or obesity. Some previous study [33] found an association between poor sleep quality and having obesity, while this study did not find such an association.…”
Section: Discussioncontrasting
confidence: 99%
“…Obesity is linked to a number of chronic conditions such as hypertension, type 2 diabetes mellitus, and dyslipidaemia [3] , [29] . Physical and mental health status risk factors for obesity include poor self-reported health status [28] , depression [30] , [31] , lower life satisfaction [32] , poor sleep quality [33] and greater happiness [34] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that poor sleep quality significantly affects BMI. 36 37 The results of the present study support this conclusion. A plausible explanation is that sleep disturbances rather than sleep duration may contribute to overweight and obesity, but further studies of the biological mechanisms are needed.…”
Section: Discussionsupporting
confidence: 87%
“…Overweight or obese people are more prone to develop prehypertension and hyperglycemia [ 9 , 10 ] than the general population. Recent studies have shown that adult men with obesity and overweight problems have a lower sleep quality than those of adult men in other body mass index (BMI) groups [ 11 ]. Obesity also worsens children’s cardio-metabolic health in their adulthood [ 12 ] and increases comorbidities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%